Exploring Visual Spatial Intelligence: How Students Approach Geometry Problem Solving - Muhammad Syarifuddin Rahman; Nurfaida Tasni; Haruna Abubakar Haruna; Cris T. Zita; Andi Asrifan (Sriwijaya University Learning and Education International Journal, 2025)
The purpose of this study was to describe the application of students' visual-spatial intelligence in solving geometry problems. Visual-spatial intelligence refers to an individual's ability to understand, visualize, and manipulate information in visual and spatial forms. This study employed a qualitative approach with a descriptive-analytical method. Data were collected using geometry test items and interview protocols, and analyzed through data condensation, data display, and conclusion drawing. The findings revealed that students' imagination skills in visualizing geometric shapes and understanding dimensional changes were still suboptimal. While students were able to recognize mathematical patterns and correctly apply volume formulas, they experienced difficulties in representing overall changes in volume. These results highlight the need for more effective instructional strategies to enhance students' visual-spatial intelligence, enabling them to solve more complex geometry problems with greater accuracy and understanding.